2001
DOI: 10.1021/jo001144z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Steric Effects in Thermal Denitrosation of N-Nitrosoamides

Abstract: N-Alkyl-N-nitrosoamides undergo competitive reactions whose rates are dependent upon the interplay of a number of factors. There already exists a significant body of work delineating the effects of pH on the partitioning of the nitrosoamides along their deaminative (-N(2)) and denitrosative (-"NO(+)") pathways. In this paper, the issue of pH dependence is discussed with particular attention to nitrosoamide decompositions in nonaqueous media. The role of the acidity of the medium in the partitioning of the nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…During the course of our studies, we found limited success for intermolecular C–H abstraction using N -nitrososulfonamides as radical precursors but found them to be effective transnitrosating reagents. Although this type of reactivity has been reported, a well known limitation of N -nitrososulfonamides as transnitrosating reagents is their propensity for thermal decomposition . In fact, N -methyl- N -nitroso- p -toluenesulfonamide (Diazald) is a well-known commercial reagent that requires only mild heating under basic conditions to generate an equivalent of diazomethane.…”
supporting
confidence: 69%
“…During the course of our studies, we found limited success for intermolecular C–H abstraction using N -nitrososulfonamides as radical precursors but found them to be effective transnitrosating reagents. Although this type of reactivity has been reported, a well known limitation of N -nitrososulfonamides as transnitrosating reagents is their propensity for thermal decomposition . In fact, N -methyl- N -nitroso- p -toluenesulfonamide (Diazald) is a well-known commercial reagent that requires only mild heating under basic conditions to generate an equivalent of diazomethane.…”
supporting
confidence: 69%
“…Darbeau, et al recently examined the classical roles of steric and electronic (internal) factors on the thermal denitrosations of N-nitrosoamides (11). A series of N-benzyl-N-nitrosocarboxamides and N-benzyl-N-nitrososulfonamides were decomposed in CDCl 3 at 608C.…”
Section: Electronic and Steric Effects In Thermal Denitrosation Of N-mentioning
confidence: 99%
“…N-nitrosodichloroacetamides, which are not as electron deficient as the trifluoroanalogues, avoid these problems by being stable to the conditions of the nitrosylation step and being able to be extracted from the acetic acid solvent into a nonpolar solvent that enables a cleaner rearrangement. As a side note, thermal denitrosylation of N-nitrosoacetamides to form amides has been described, [14] but typically this pathway is favored by acidic or basic aqueous solvents; we did not observe substantial denitrosylation in any of our experiments (<2% produced by 1 …”
Section: Mechanismmentioning
confidence: 48%